The Future of the New: Artistic Innovation in Times of Social Acceleration - Lijster, Thijs -1981 (Amsterdam Valiz, 2018)
In The Future of the New: Artistic Innovation in Times of Social Acceleration artists, theorists, and professionals working the art field reflect on the role of the arts in a world that is speeding up and changing through joint forces of globalization, digitization, commodification, and financialization. Can artistic innovation still function as a source of critique? How do artists, theorists, and art organizations deal with the changing role of and discourse on innovation? Should we look for alternative ways to innovate, or should we change our discourse and look for other (new!) ways to talk about the new? Combining timely analyses of contemporary art and inspiring visions for the future, The Future of the New attempts to set the agenda for the debate on the function, value and future of artistic innovation.
Contributors: Lietje Bauwens, Franco 'Bifo' Berardi, Robin Celikates, Wouter de Raeve, Elena Esposito, Boris Groys, Alice Haddad, Akiem Helmling, Bojana Kunst, Thijs Lijster, Suhail Malik, Benjamin Noys, Hartmut Rosa, Nick Srnicek Carolyn F. Strauss, Rolando Vázquez, Alex Williams
Keywords: Artistic research; Technology; Imagination; Esthetics; Crescendo